An Extended Thickness-Dependent Moisture Absorption Model for Unidirectional Carbon/Epoxy Composites - Azizan, Azisyahirah; Johar, Mahzan; Karam Singh, Salvinder Singh; Abdullah, Shahrum; Koloor, Seyed Saeid Rahimian; Petrů, Michal; Wong, King Jye; Tamin, Mohd Nasir (Polymers, 2021)
Moisture absorption tests for materials that exhibit non-Fickian behavior generally require a relatively long period to reach saturation. Therefore, it would be beneficial to establish a relationship between the moisture content and the thickness to minimize the experimental time and cost. This research characterizes the moisture absorption behavior of AS4/8552 carbon/epoxy composites. Specimens were prepared at 4, 8, and 16 plies and immersed in distilled water at 60 °C. The relationship between the non-Fickian parameters (Fickian to non-Fickian maximum moisture content ratio ϕ, non-Fickian diffusivity per square thickness α, and non-Fickian initiation time to) and thickness was characterized using a thickness-dependent model. A comparison with other materials revealed that all three non-Fickian parameters are able to be fitted using a power law. Nevertheless, the upper boundary for the applicability of this model was not determined in this study. The Weibull distribution plots indicate that the probability of non-Fickian moisture absorption is influenced by ϕ and α at approximately 62% within a normalized thickness range of 2-3. In regards to to, it is 82% at a normalized thickness of 6. Therefore, the Weibull distribution is proposed for the assessment of non-Fickian moisture absorption based on the material's thickness.
Keywords: moisture absorption; Weibull; thickness-dependent; carbon/epoxy composite; non-Fickian